2004
DOI: 10.1196/annals.1337.008
|View full text |Cite
|
Sign up to set email alerts
|

An Insulin‐like Growth Factor 2‐Derived Self‐Antigen Inducing a Regulatory Cytokine Profile after Presentation to Peripheral Blood Mononuclear Cells from DQ8+ Type 1 Diabetic Adolescents: Preliminary Design of a Thymus‐Based Tolerogenic Self‐Vaccination

Abstract: This work aims to evaluate the potential use of insulin-like growth factor 2 (IGF-2) as the dominant thymic self-antigen precursor of the insulin family in designing a tolerogenic approach to type 1 diabetes (T1D) prevention. This evaluation was primarily based on cytokine profile driven by MHC presentation of insulin and IGF-2-derived antigens to PBMC cultures derived from 16 T1D DQ8 + adolescents. Insulin B9-23, one dominant ␤-cell autoantigen, and the homologous sequence B11-25 of IGF-2 display the same aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Our current in‐depth knowledge of thymus physiology and physiopathology has now been translated into the design of innovative tolerogenic and regulatory strategies aimed at restoring central self‐tolerance that is absent or defective in autoimmunity 40–42 . The concept of negative self‐vaccination has been proposed and is based both on the competition between thymic self‐antigens and peripheral target antigens for presentation by MHC proteins, as well as a tolerogenic response—including recruitment of T reg cells—induced by MHC presentation of thymic self‐epitopes 43,44 . With this perspective, a research consortium in Wallonia is working on the development of a negative/tolerogenic self‐vaccination with the thymic self‐peptides related to T1D (Tolediab project).…”
Section: The Escape From Central Self‐tolerance As a Primary Event Inmentioning
confidence: 99%
“…Our current in‐depth knowledge of thymus physiology and physiopathology has now been translated into the design of innovative tolerogenic and regulatory strategies aimed at restoring central self‐tolerance that is absent or defective in autoimmunity 40–42 . The concept of negative self‐vaccination has been proposed and is based both on the competition between thymic self‐antigens and peripheral target antigens for presentation by MHC proteins, as well as a tolerogenic response—including recruitment of T reg cells—induced by MHC presentation of thymic self‐epitopes 43,44 . With this perspective, a research consortium in Wallonia is working on the development of a negative/tolerogenic self‐vaccination with the thymic self‐peptides related to T1D (Tolediab project).…”
Section: The Escape From Central Self‐tolerance As a Primary Event Inmentioning
confidence: 99%
“…Individuals with MHCII DR3-DQ2 and DR4-DQ8 haplotypes have a significantly higher risk of T1D and DQ6 (DQA1 ∗ 0102/DQB1 ∗ 0602) is dominantly protective in Caucasians, Mexicans, and other Latin American populations (13). A number of studies have demonstrated the peptide-binding specificity of DQ8 as well as T cells from T1D that recognize pancreatic autoantigens presented by DQ8 (48). Compared with the DQ2 and DQ8 homozygous individuals, DR3-DQ2/DR4-DQ8 heterozygotes (DRB1 ∗ 0301-DQA1 ∗ 0501-DQB1 ∗ 0201/DRB1 ∗ 04-DQA1 ∗ 0301-DQB1 ∗ 0302) have the highest risk in whites of European and Northern African decent (9).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the close homology and cross-tolerance between insulin and IGF-2, a novel type of negative/tolerogenic self-vaccination is currently developed for prevention and cure of T1D (23). Indeed, administration of IGF-2-derived self-antigens (B11-25 sequence) to peripheral blood mononuclear cells from DQ8 ϩ type 1 diabetic patients seems to be an efficient approach in T1D prevention, since it elicits a tolerogenic/regulatory cytokine profile (interleukin-10 [IL-10], IL-10/ gamma interferon [IFN-␥], and IL-4) statistically different from the one induced by Ins B9-23 (19). This issue is currently investigated by vaccination of NOD mice with recombinant human IGF-2 alone or in combination with adjuvants (20).…”
mentioning
confidence: 99%